2021
DOI: 10.1016/j.expneurol.2020.113513
|View full text |Cite
|
Sign up to set email alerts
|

Subthalamic beta oscillations correlate with dopaminergic degeneration in experimental parkinsonism

Abstract: Excessive beta activity has been shown in local field potential recordings from the cortico-basal ganglia loop of Parkinson's disease patients and in its various animal models. Recent evidence suggests that enhanced beta oscillations may play a central role in the pathophysiology of the disorder and that beta activity may be directly linked to the motor impairment. However, the temporal evolution of exaggerated beta oscillations during the ongoing dopaminergic neurodegeneration and its relation to the motor im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 64 publications
(87 reference statements)
2
21
1
Order By: Relevance
“…In animal models of Parkinsonism, it has been demonstrated that increasing beta band power and longer beta bursts are markers of progressive Parkinsonian pathophysiology. [15][16][17][18][19] There have been repeated demonstrations of the short-term effect of therapy (both DBS and medication) on the beta oscillopathy. 7,11,44 The only longitudinal studies to date tracking beta power have been limited to the first year post-DBS and have each shown either a reduction or stability of beta over that time.…”
Section: Lack Of Progression Of Beta Oscillopathy Following Chronic Stn Dbsmentioning
confidence: 99%
See 2 more Smart Citations
“…In animal models of Parkinsonism, it has been demonstrated that increasing beta band power and longer beta bursts are markers of progressive Parkinsonian pathophysiology. [15][16][17][18][19] There have been repeated demonstrations of the short-term effect of therapy (both DBS and medication) on the beta oscillopathy. 7,11,44 The only longitudinal studies to date tracking beta power have been limited to the first year post-DBS and have each shown either a reduction or stability of beta over that time.…”
Section: Lack Of Progression Of Beta Oscillopathy Following Chronic Stn Dbsmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14] Increasing beta power over time is linked to progressive Parkinsonian pathophysiology in neural recordings from both non-human primate and rodent models of progressive Parkinsonism. [15][16][17][18][19] Although a causal link between beta power and PD impairment in humans is still lacking, resting state beta power is greater in the more affected compared to the lesser affected STN, 6 and beta power has been found to increase over time in the untreated STN in two individuals with Parkinson's disease, further suggesting a relationship to disease progression. 20 Beta power was attenuated and burst durations were shortened during short periods of high frequency STN DBS in a dose-dependent manner while improving motor disability 14,21,22 and for a period after STN DBS was turned off, [23][24][25] particularly when neurostimulation targeted the sensorimotor portion of the STN.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A further consideration for future work is the role of dopamine in mediating anxiety-related changes in alpha-beta activity during Bayesian PC. Dopamine is considered a relevant signal encoding the precision of beliefs during reward learning (FitzGerald et al, 2015) and is associated with sensorimotor beta oscillations in research on Parkinson’s (Haumesser et al, 2021; Jenkinson and Brown 2011). Dopamine also plays an important modulatory role in fear and anxiety disorders (de la Mora et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Since the finding that the subthalamic nucleus (STN) shows exaggerated and synchronized oscillatory activity in the beta frequency range in PD patients 5,6 , the majority of neurophysiological research in this field has postulated beta activity as a stereotypical biomarker across species from animals [7][8][9][10] to PD patients. [11][12][13][14] Abnormal beta power was shown to correlate with the clinical severity of parkinsonian motor symptoms.…”
Section: Introductionmentioning
confidence: 99%